CHRISTIYAN-ECZISTENT IMPERATIVES CREATION OF OLGA COBILYANSKA (from the antimilitaristic cycle of short stories and stories) - Savka, B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the comparative analysis in “little prose” antiwar thematics by O. Kobylianska in the Christian-and-existential opinion. Particularly the implementation of national identity ideas in the evolvement of the plot image-and-personage.